ENVIRONMENTAL IMPACTS OF ECONOMIC ACTIVITIES ON QUALITY OF THUY TRIEU LAGOON - CAM RANH BAY - Thom, Pham Van; Vinh, Le Thi; Thu, Nguyen Hong; Kiem, Duong Trong; Tam, Pham Huu (Vietnam Journal of Marine Science and Technology, 2006)
ENVIRONMENTAL IMPACTS OF ECONOMIC ACTIVITIES ON QUALITY OF THUY TRIEU LAGOON - CAM RANH BAY